2019
DOI: 10.1021/acs.jpcc.9b03184
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Electron Harvesting in Robust Titanium Nitride Nanostructures

Abstract: Titanium nitride (TiN) continues to prove itself as an inexpensive, robust, and efficient alternative to gold in plasmonic applications. Notably, TiN has improved hot electron harvesting and photocatalytic abilities compared to gold systems, which we recently attributed to the role of oxygen in TiN and its native semiconducting TiO2-x surface layer. Here, we explore the role of localized surface plasmon resonances (LSPRs) on electron harvesting across the TiN/TiO2-x interface and probe the resilience of TiN na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…[ 1–9 ] Titanium nitride (TiN), zirconium nitride (ZrN), and other plasmonic nitrides such as hafnium nitride (HfN) and tantalum nitride (TaN) are particularly attractive due to their high melting points that bolster stability at higher ambient temperatures [ 10–12 ] and/or under higher laser irradiation intensities, [ 13–16 ] in addition to their mechanical hardness [ 17,18 ] and complementary metal‐oxide‐semiconductor compatibility. [ 19–21 ] Recent work has demonstrated that TiN shows strong local heating compared to Au, [ 22–24 ] which may be exploited for photothermal therapy, [ 25,26 ] shape‐memory effects, [ 27 ] thermochromic windows, [ 28 ] photoreactions, [ 29–32 ] heat transducers or thermophotovoltaic materials, [ 22,33–37 ] or photodetection. [ 38 ] Implicit in these observations and devices are very different optical responses of metallic nitrides compared to gold—the most similar classical plasmonic material—particularly with regard to the dissipation of heat.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–9 ] Titanium nitride (TiN), zirconium nitride (ZrN), and other plasmonic nitrides such as hafnium nitride (HfN) and tantalum nitride (TaN) are particularly attractive due to their high melting points that bolster stability at higher ambient temperatures [ 10–12 ] and/or under higher laser irradiation intensities, [ 13–16 ] in addition to their mechanical hardness [ 17,18 ] and complementary metal‐oxide‐semiconductor compatibility. [ 19–21 ] Recent work has demonstrated that TiN shows strong local heating compared to Au, [ 22–24 ] which may be exploited for photothermal therapy, [ 25,26 ] shape‐memory effects, [ 27 ] thermochromic windows, [ 28 ] photoreactions, [ 29–32 ] heat transducers or thermophotovoltaic materials, [ 22,33–37 ] or photodetection. [ 38 ] Implicit in these observations and devices are very different optical responses of metallic nitrides compared to gold—the most similar classical plasmonic material—particularly with regard to the dissipation of heat.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we compare the electron extraction efficiency across Au/TiO2 and titanium oxynitride/TiO2-x interfaces, where in the latter case the spontaneously forming oxide layer (TiO2-x) creates a metal-semiconductor contact. Time-resolved pump-probe spectroscopy is used to study the electron recombination rates in both cases [12,13]. Unlike the nanosecond recombination lifetimes in Au/TiO2, we find a bottleneck in the electron relaxation in the TiON system, which we explain using a trap-mediated recombination model.…”
mentioning
confidence: 71%
“…53 After loading of Pt nanoparticles, all TiN peaks exhibit blue shift indicating that the nitride lattice is marginally perturbed due to the bonding with surface Pt atoms. [54][55] Besides, two new characteristic peaks at 174 and 721 cm -1 , which belong to Pt-Pt stretching vibrations and Pt-O vibrations in Pt nanoparticles. [56][57][58] and Pt 4f 5/2 , respectively.…”
Section: Photoelectrochemical (Pec) Propertiesmentioning
confidence: 98%